Sárköz, Südungarn: Das Neolithikum in Transdanubien - Bánffy, Eszter; Rassmann, Knut (e-Forschungsberichte des DAI, 2023)
Since 2011 the Romano-Germanic Commission (RGK) engages in geomagnetic prospections on Hungarian multi-period settlements. Our study began with fieldwork at the Alsónyék-Bátaszék and Tolna-Mözs sites. In die following years we continued the survey on both sites, enlarging the program on the tell settlement of Fajsz-Kovácshalom and on other sites in eastern Hungary. Our main goal is to discuss the combination of excavation data and geomagnetics which provides a great opportunity to estimate the size of the settlements as well as to study their internal structures. The report focuses on the Alsónyék-Bátaszék and Tolna-Mözs site where numerous settlement remains and a large number of Late Neolithic burials were unearthed. Excellent prerequisites for prospection campaigns include rich comparative excavation data which are useful for understanding and interpreting geomagnetic anomalies from the unexcavated areas.